The sintering temperature effect on electrochemical properties of Ce(0.8)Sm(0.05)Ca(0.15)O(2-δ) (SCDC)-La(0.6)Sr(0.4)Co(0.2)Fe(0.8)O(3-δ) (LSCF) heterostructure pellet - Nie, Xiyu (Nanoscale Res Lett, 2019)
Recently, semiconductor-ionic materials (SIMs) have emerged as new functional materials, which possessed high ionic conductivity with successful applications as the electrolyte in advanced low-temperature solid oxide fuel cells (LT-SOFCs). In order to reveal the ion-conducting mechanism in SIM, a typical SIM pellet consisted of semiconductor La(0.6)Sr(0.4)Co(0.2)Fe(0.8)O(3-δ) (LSCF) and ionic conductor Sm and Ca Co-doped ceria Ce(0.8)Sm(0.05)Ca(0.15)O(2-δ) (SCDC) are suffered from sintering at different temperatures. It has been found that the performance of LSCF-SCDC electrolyte fuel cell decreases with the sintering temperature, the cell assembled from LSCF-SCDC pellet sintered at 600 °C exhibits a peak power density (P(max)) of 543 mW/cm(2) at 550 °C and also excellent performance of 312 mW/cm(2) even at LT (500 °C). On the contrary, devices based on 1000 °C pellet presented a poor P(max) of 106 mW/cm(2). The performance difference may result from the diverse ionic conductivity of SIM pellet through different temperatures sintering. The high-temperature sintering could severely destroy the interface between SCDC and LSCF, which provide fast transport pathways for oxygen ions conduction. Such phenomenon provides direct and strong evidence for the interfacial conduction in LSCF-SCDC SIMs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-019-2979-x) contains supplementary material, which is available to authorized users.